Potassium-competitive Acid Blockers: A New Therapeutic Strategy for Helicobacter pylori Eradication - Byeong Yun Ahn; Soo-Jeong Cho (Yong Chan Lee, 2023)
The escalating prevalence of clarithromycin resistance in cases of Helicobacter pylori, insufficient acid suppression, and pharmacodynamic variations secondary to inter-individual differences in CYP2C19 polymorphism collectively contribute to suboptimal eradication rates observed with proton pump inhibitor (PPI)-based therapy. Compared with PPIs, potassium-competitive acid blockers (PCABs) produce rapid, potent, and long-lasting suppression of gastric acid through reversible inhibition of gastric H+, K+-ATPase. PCAB-based therapy results in significant inhibition of acid secretion and has therefore emerged as a novel and effective approach for H. pylori eradication. In this study, we review the efficacy and safety profile of PCAB-based eradication regimens comprising vonoprazan, tegoprazan, and fexuprazan.